Analysis of the Influence of Amenity and Tourist Attractions on the Satisfaction of Inbound Muslim Tourists Visiting Halal-Based Tourist Destinations in Super Tourism Area Lake Toba Samosir - Surya, Elfitra Desy; Saragih, Megasari Gusandra; Siregar, Nur Afrina (Budapest International Research and Critics University, 2021)
This research aims to know the Tourism amenity, tourist attractions on the satisfaction of Inbound Muslim tourists visiting the halal-based tourist destination area in the Super Lake Toba Area. The sample in this study was as many as 100 samples obtained from 5x the number of people indicators with random sampling technique. An analysis of the data is conducted using multiple linear regressions. The results of this study is tourism amenity have positive and significant effect on the satisfaction of tourists visiting halal-based tourist destinations in the super area of Lake Toba. The results of this study is a tourist attraction have positive and significant effect on the satisfaction of tourists visiting halal-based tourist destinations in the super area of Lake Toba. R-Square for variable Y is 0.604. The acquisition of the value explains that the percentage of the magnitude of competence Y can be explained by X1 and X2 of 60.4%.